Historical Relationship of Premature Labor and Low Born Weight with Nutrition Status of Children Under Three Years Old - Lestari, Heni Eka Puji; Villasari, Asasih; Kartika, K (Universitas Muhammadiyah Surakarta, 2020)
Purpose: Determine the relationship between low birth weight (LBW) history and prematurity history with the nutritional status of three-year-old babies in Ngumbul Tulakan Village, Pacitan.Methodology: This research is a descriptive analytic using a cross sectional approach. Population in this study were 123 babies three years old in Ngumbul Tulakan Pacitan Village. The sampling technique used was simple random sampling, with a sample size of 94 three-year-old baby. Data collection using the observation sheet. Data analysis used Chi square test with ɑ = 0.05.Results: The results of this study were a small proportion of three-year-old babies with a history of low birth weight (LBW) in the village of Ngumbul Tulakan, Pacitan, there were 24 children (25.5%). Three year old babies with history of premature were 20.2% (as many as 19 three-year-old baby) in Ngumbul Tulakan Pacitan village. The nutritional status of three-year-old babies in the village of Gumbul Tulakan, Pacitan, is mostly normal (76.6%). The results of statistical tests showed that there was a relationship between LBW history with the nutritional status of three-year-old infants in Ngumbul Tulakan Village, Pacitan with a value of ρ value of 0.00. There is a relationship between a history of prematurity and the nutritional status of three-year-old baby in Ngumbul Tulakan Village, Pacitan with a value of ρ value of 0.00Conclusion: It is recommended that mothers take their three-year-old babies to the posyandu regularly to monitor their growth and development and provide a balanced nutritional intake according to the needs of a three-year-old baby.